2021
DOI: 10.1155/2021/5529981
|View full text |Cite|
|
Sign up to set email alerts
|

Falling-Point Recognition and Scoring Algorithm in Table Tennis Using Dual-Channel Target Motion Detection

Abstract: In table tennis, the ball has numerous characteristics of high speed, small size, and changeable trajectory. Due to these characteristics, the human eye often cannot accurately judge the ball’s movement and position, leading to the problem of precise detection of the ball’s falling point and movement tracking. In sports, the use of machine learning for locating and detecting the ball and the use of deep learning for reconstructing and displaying the ball’s trajectories are considered futuristic technologies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Reno 14 determines whether the image contains tennis balls by classifying small pieces of the input image, which has a high detection accuracy. Yang 15 used a 3D neural network to fuse the table tennis ball feature information obtained from different channels to identify table tennis balls and table tennis ball landing points using fully connected layers and this method has good results in table tennis ball recognition. Calandre 16 used a single camera to estimate the size of the ball to obtain the distance from the ball to the camera and used a 2D CNN network for 3D trajectory analysis of the ball, which performed well on the dataset.…”
Section: A Study On Table Tennis Landing Point Detection Algorithm Ba...mentioning
confidence: 99%
“…Reno 14 determines whether the image contains tennis balls by classifying small pieces of the input image, which has a high detection accuracy. Yang 15 used a 3D neural network to fuse the table tennis ball feature information obtained from different channels to identify table tennis balls and table tennis ball landing points using fully connected layers and this method has good results in table tennis ball recognition. Calandre 16 used a single camera to estimate the size of the ball to obtain the distance from the ball to the camera and used a 2D CNN network for 3D trajectory analysis of the ball, which performed well on the dataset.…”
Section: A Study On Table Tennis Landing Point Detection Algorithm Ba...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%